2013
DOI: 10.1074/jbc.m113.458737
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Acetyltransferase GCN5 Potentiates the Growth of Non-small Cell Lung Cancer via Promotion of E2F1, Cyclin D1, and Cyclin E1 Expression

Abstract: Background:The role of the lysine acetyltransferase GCN5 in cancer development remains largely unknown. Results: GCN5 expression correlates with lung cancer tumor size, directly enhances the expression of E2F1, cyclin E1, and cyclin D1, and potentiates lung cancer growth. Conclusion: GCN5 potentiates lung cancer growth in an E2F1-dependent manner. Significance: GCN5 is critical for lung cancer growth and represents a potential target for the treatment of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 46 publications
3
115
0
Order By: Relevance
“…GCN5 have been documented for its functions in transcription [21] and cell cycle regulation [25], as well as cellular transformation and cancer cell survival [35,36]. Recently, it has been reported that GCN5 is able to potentiate cell growth in the development of non-small cell lung cancer [26]. Interestingly, in this study we found a novel role of GCN5 in modulation of breast cancer cell migration mediated by HBXIP.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…GCN5 have been documented for its functions in transcription [21] and cell cycle regulation [25], as well as cellular transformation and cancer cell survival [35,36]. Recently, it has been reported that GCN5 is able to potentiate cell growth in the development of non-small cell lung cancer [26]. Interestingly, in this study we found a novel role of GCN5 in modulation of breast cancer cell migration mediated by HBXIP.…”
Section: Discussionmentioning
confidence: 68%
“…In cell migration, this subset of acetylated microtubules extends into protrusions [17], regulates cell polarization [18], and is required for persistent directional movement [19,20]. GCN5 (general control nonderepressible 5) is the first identified transcription-related histone acetyltransferase and has been implicated in diverse cellular processes including transcription [21,22], DNA repair [23], nucleosome assembly [24], cell cycle regulation [25], and cancer cell growth [26]. Additionally, it has been reported that GCN5 acts as aAbbreviations: HBXIP, hepatitis B X-interacting protein; GCN5, general control non-derepressible 5; aTAT, a-tubulin acetyltransferase.…”
Section: Introductionmentioning
confidence: 99%
“…For example, GCN5 was found to be highly expressed in non-small cell lung cancer. Its expression correlated with tumor size, and it was recruited by E2F1 to induce A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 41 histone acetylation and subsequent activation of E2F1 and the mitotic genes cyclin D1 and cyclin E1 [414].…”
Section: Gcn5mentioning
confidence: 98%
“…Gcn5 could also interact with acetylated histones directly via its bromodomain to target HAT activity to chromatin bound substrates. Intriguingly, human GCN5 is overexpressed in lung cancer, with its expression level correlating with tumor size (58). Although it is unclear what percentage of this protein is incorporated into complexes, it is conceivable that some effects of hGCN5 overexpression may stem from aberrant acetylation of select non-histone substrates that hGCN5 can target independently of its normal interaction partners.…”
Section: Fig 7 Ada2 Selectively Regulates Gcn5-dependent Acetylationsmentioning
confidence: 99%